Electron attachment to atomic hydrogen on the surface of liquid 4He: Электроны над жидким гелием - Arai, Toshikazu; Yayama, Hideki; Kono, Kimitoshi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We demonstrate a possibility that helium surface electrons at cryogenic temperatures can be used as a new source of very low energy electrons. Since both electrons (e-) and hydrogen atoms (H) are bound on liquid helium surface, two-dimensional mixture gas of these two species is available on the surface. We found that low energy collision of e- and H drives electron attachment to form a negative hydrogen ion (H-) in the mixture. From our temperature dependence measurement of the reaction rate, it was found that another H atom participate in the reaction. Namely, the reaction is expressed as H + H + e- + H- + H. Possible reaction mechanisms are discussed in terms of direct three-body process and dissociative attachment process. Measurements in applied magnetic field (B) show that the reaction rate coefficient is suppressed as ~B-2. This implies that electron spin singlet collision is relevant for electron attachment.